Oropharyngeal colonization by Haemophilus influenzae in healthy children from Taubaté (São Paulo), prior to the Haemophilus influenzae type b vaccination program in Brazil - Bricks,Lucia Ferro (2004)
Haemophilus influenzae is one of the most important bacterial agents of otitis and sinusitis. H. influenzae type b (Hib) is one of the main causes of meningitis, pneumonia, and septicemia in nonvaccinated children under 6 years of age. The aims of this study were to determine the prevalence of H. influenzae and Hib oropharyngeal colonization prior to the onset of the Hib vaccination program in Brazil in previously healthy children and to assess the susceptibility profile of this microorganism to a selected group of antimicrobials that are used to treat acute respiratory infections. METHOD: Cultures of Haemophilus influenzae were made from oropharynx swabs from 987 children under 6 years of age who were enrolled in 29 day-care centers in Taubaté (a city of São Paulo state, Brazil) between July and December 1998. RESULTS: The prevalence of H. influenzae carriers was 17.4%, and only 5.5% of the strains were beta-lactamase producers. The prevalence of Hib carriers was high, 7.3% on average (range, 0.0 - 33.3%). CONCLUSIONS: The low prevalence of colonization by penicillin-resistant strains indicates that it is not necessary to substitute ampicilin or amoxicilin to effectively treat otitis and sinusitis caused by H. influenzae in Taubaté.